Constructions around the Church of the Redeemer in Ani - Kazaryan, Armen; Baeva, Olga (project baikal, 2026)
The study of groups of buildings around one of the largest churches in the medieval Armenian capital of Ani is based on written sources and excavation findings from the XII campaign of 1913 of the Ani Archaeological Expedition led by N. J. Marr. A comparison of the data available in these documents, as well as the search and analysis of the current state of some buildings, lead to a new understanding of the structure of the urban area, its dominants and the changes that have taken place over three or four centuries.
Keywords: Ani; medieval urban environment; dwellings; churches; mausoleum; N. J. Marr expedition; archaeological excavations